Description Of Nutritional Status In Toddlers At Romana Tanjung Anoms Clinic, Pancur Batu District Year 2022: GAMBARAN STATUS GIZI PADA BALITA DI KLINIK ROMANA TANJUNG ANOM KECAMATAN PANCUR BATU TAHUN 2022 - Lase, Merci Andriani; Sigalingging, Vina YS.; Siallagan, Ance M. (Institute of Accounting Research and Novation (IARN), 2024)
The nutritional status of children under five is the condition of the body of a toddler with the fulfillment of balanced nutrition in the body of a toddler, things that every parent must know about the growth and development of children at the age of toddlers. Nutritional status is influenced by the availability of food at the family level, family parenting, environmental health, basic health services, family culture, socioeconomic, education level, and knowledge. This study aims to determine the nutritional status of toddlers at Romana Tanjung Anom Clinic, Pancur Batu District 2022. The type of design in this study is descriptive. The sampling technique in this research is total sampling. The results show that the nutritional status of toddlers at Romana Tanjung Anom Clinic, Pancur Batu District 2022, is mostly in the good category with 62 respondents (42.5%) where the nutrition of the toddlers is fulfilled according to their needs and also when the posyandu is always given additional food and information obtained during the posyandu. Parents should continue to maintain and monitor the nutritional development and growth of toddlers and be more active in seeking health information about toddlers.